The influence of deposition temperature on the morphology and corrosion resistance of zinc phosphate coating on mild steel - Khalid, Abdalla; Azmi, Rahmat, Prof. Madya Dr.; Azizan, Aziz, Assoc. Prof. Dr. (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/